Optimization of the parameters of resistance spot welding at an automotive industry through the analysis of experiments and response surface methodology - Silveira de Souza, Mayra Tereza; Fernandes, Marcelo Machado [UNESP]; Miranda, Rafael De Carvalho (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2013)
One way to achieve the competitive characteristics or critical factors and meet the needs and expectations of consumers is through the application of design techniques and analysis of experiments and response surface methodology, since the combined use of these techniques, enables the determination of optimal settings for obtaining the desired result. In this sense this paper aims to apply these techniques to optimization of the parameters involved in a resistance spot welding process. As part of this goal, an application is developed with the technique of full factorial design, in order to discover which parameters involved in the process in question (power, strength, weld time and pre weld time), actually promote significant effect on response (tensile strength). With the experiments and analyzing the data generated by the software MINITAB, it appears that only the current and strength parameters are significant. Thereafter, the technique of central composite design is used, the stationary point is determined and finally the analysis of eigenvalues of the Hessian matrix is conducted to determine the current and strength values that promote better performance in terms of tensile strength.
Otimização dos parâmetros de soldagem a ponto por resistência em uma indústria automotiva por meio da análise de experimentos e metodologia de superfície de resposta
Keywords: Design and analysis of experiments; Optimization; Resistance spot welding process; Response surface methodology